Dosing errors in total parenteral nutrition prescriptions at a specialized cancer care hospital of Lahore: The role of clinical pharmacist. (April 2021) - Akbar, Zunaira; Saeed, Hamid; Saleem, Zikria; Andleeb, Sidra
Study objective: To determine the role of pharmacist in identifying the frequency of errors in total parenteral nutrition prescriptions in cancer patients for the years 2015 and 2016. Total parenteral nutrition has a high potential for medical errors because of its complex composition, thus leading to severe complications. Pharmacist review of the prescriptions reduces the risk of inappropriate prescribing, preparation, and administration of parenteral nutrition. Methodology: An observational study was performed by collecting data of total parenteral nutrition prescriptions of 71 patients for the last two years from Pharmacy Department of specialized cancer care hospital. Results: It was found that the frequency of dosing errors and incomplete prescriptions was higher in 2015 compared to 2016. Additionally, the frequency of macro and micronutrients dosing errors were higher in adults (23.4% and 66.2%) compared to pediatrics (14.6% and 46.6%). Furthermore, the frequency of illegible prescriptions was higher (5.03%) in year 2016 as compared to year 2015 (1.64%). Nevertheless, such dose interventions improved patient's weight (20%) and promoted enteral feeding (42.3%). Major complication was hypophosphatemia (39.4%) followed by hyperglycemia (10%) and catheter-induced infection, i.e. sepsis (4.2%). Conclusion: In conclusion, data suggested that pharmacist played instrumental role in identifying and rectifying total parenteral nutrition dosing errors for both micronutrients and macronutrients—with higher frequency in 2015 compared to 2016, leading to improvements in total parenteral nutrition-related complications and switches to enteral feeding.